Analisis Perlindungan HAM Dalam Konteks Penerapan Pasal 3 UU No. 39 Tahun 1999 Tentang Hak Asasi Manusia - Al Firman Mangunsong; Dewi Romantika Tinambunan; Jojor Mindo Manullang; Mima Defliyanti Saragih; Murniwati Lase; Ture Ayu Situmeang; Ramsul Yandi Nababan (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Human rights are a set of rights inherent in every human being as a creature of God Almighty and are His gift which must be respected and upheld, and protected by the state, law, government and every person for the sake of honor and protection of human dignity. Protection of human rights is a very crucial and important foundation for creating a just, peaceful and civilized society. In this case, law has an important role in becoming an instrument that can become the basis for creating protection and guarantees for the rights of every human being. This research was conducted with the aim of finding out how human rights protection is carried out in the context of implementing Article 3 of Law no. 39 of 1999 concerning Human Rights. The method used in this research is the literature study research method. This research produces insight into how the state carries out and provides protection for human rights.